The Clinical Outcome Study for dysferlinopathy: An international multicenter study. (August 2016) - Harris, Elizabeth; Bladen, Catherine L.; Mayhew, Anna; James, Meredith; Bettinson, Karen; Moore, Ursula; Smith, Fiona E.; Rufibach, Laura; Cnaan, Avital; Bharucha-Goebel, Diana X.; Blamire, Andrew M.; Bravver, Elena; et al.
Abstract : Objective: To describe the baseline clinical and functional characteristics of an international cohort of 193 patients with dysferlinopathy. Methods: The Clinical Outcome Study for dysferlinopathy (COS) is an international multicenter study of this disease, evaluating patients with genetically confirmed dysferlinopathy over 3 years. We present a cross-sectional analysis of 193 patients derived from their baseline clinical and functional assessments. Results: There is a high degree of variability in disease onset, pattern of weakness, and rate of progression. No factor, such as mutation class, protein expression, or age at onset, accounted for this variability. Among patients with clinical diagnoses of Miyoshi myopathy or limb-girdle muscular dystrophy, clinical presentation and examination was not strikingly different. Respiratory impairment and cardiac dysfunction were observed in a minority of patients. A substantial delay in diagnosis was previously common but has been steadily reducing, suggesting increasing awareness of dysferlinopathies. Conclusions: These findings highlight crucial issues to be addressed for both optimizing clinical care and planning therapeutic trials in dysferlinopathy. This ongoing longitudinal study will provide an opportunity to further understand patterns and variability in disease progression and form the basis for trial design.